Eph-B4 regulates adaptive venous remodeling to improve arteriovenous fistula patency. Issue 1 (December 2017) - Protack, Clinton; Foster, Trenton; Hashimoto, Takuya; Yamamoto, Kota; Lee, Monica; Kraehling, Jan; Bai, Hualong; Hu, Haidi; Isaji, Toshihiko; Santana, Jeans; Wang, Mo; Sessa, William; et al.
Abstract Low rates of arteriovenous fistula (AVF) maturation prevent optimal fistula use for hemodialysis; however, the mechanism of venous remodeling in the fistula environment is not well understood. We hypothesized that the embryonic venous determinant Eph-B4 mediates AVF maturation. In human AVF and a mouse aortocaval fistula model, Eph-B4 protein expression increased in the fistula vein; expression of the arterial determinant Ephrin-B2 also increased. Stimulation of Eph-B-mediated signaling with Ephrin-B2/Fc showed improved fistula patency with less wall thickness. Mutagenesis studies showed that tyrosine-774 is critical for Eph-B4 signaling and administration of inactive Eph-B4-Y774F increased fistula wall thickness. Akt1 expression also increased in AVF; Akt1 knockout mice showed reduced fistula diameter and wall thickness. In Akt1 knockout mice, stimulation of Eph-B signaling with Ephrin-B2/Fc showed no effect on remodeling. These results show that AVF maturation is associated with acquisition of dual arteriovenous identity; increased Eph-B activity improves AVF patency. Inhibition of Akt1 function abolishes Eph-B-mediated venous remodeling suggesting that Eph-B4 regulates AVF venous adaptation through an Akt1-mediated mechanism.